2018
DOI: 10.1149/2.1211814jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthetic Parameters on Defects, Structure, and Electrochemical Properties of Layered Oxide LiNi0.80Co0.15Al0.05O2

Abstract: LiNi 0.80 Co 0.15 Al 0.05 O 2 , a cathode material of the high energy density layered oxide family, was synthesized at various time and temperature values to form single particles. The result of each synthesis condition was comprehensively characterized, demonstrating differing purity, morphology, and electrochemical properties, expanding the current knowledge of the LiNi 0.80 Co 0.15 Al 0.05 O 2 system. 800 • C was found to be the temperature in which particle growth was reliably observed. Particle size was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…One NCA material was obtained from TODA America Inc., which is termed as “TODA-NCA” in this work. The other NCA material adopted for the in situ TEM experiments is platelets (termed as “platelet NCA” in this work), which were hydrothermally synthesized via a two-step process . Ni­(NO 3 ) 2 ·6H 2 O, Co­(NO 3 ) 2 ·6H 2 O, and Al­(NO 3 ) 3 ·9H 2 O were first mixed in water using the appropriate stoichiometric ratio, followed by the addition of NaOH using a molar ratio of 1:2 in a total of 70 mL solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One NCA material was obtained from TODA America Inc., which is termed as “TODA-NCA” in this work. The other NCA material adopted for the in situ TEM experiments is platelets (termed as “platelet NCA” in this work), which were hydrothermally synthesized via a two-step process . Ni­(NO 3 ) 2 ·6H 2 O, Co­(NO 3 ) 2 ·6H 2 O, and Al­(NO 3 ) 3 ·9H 2 O were first mixed in water using the appropriate stoichiometric ratio, followed by the addition of NaOH using a molar ratio of 1:2 in a total of 70 mL solution.…”
Section: Methodsmentioning
confidence: 99%
“…The other NCA material adopted for the in situ TEM experiments is platelets (termed as "platelet NCA" in this work), which were hydrothermally synthesized via a two-step process. 58 Ni(NO 3 ) 2 •6H 2 O, Co(NO 3 ) 2 •6H 2 O, and Al(NO 3 ) 3 •9H 2 O were first mixed in water using the appropriate stoichiometric ratio, followed by the addition of NaOH using a molar ratio of 1:2 in a total of 70 mL solution. The mixture was hydrothermally treated at 160 °C for 12 h using water in a Teflonlined stainless vessel, producing the hydroxide precursor.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…LiNi 0.8 Co 0.15 Al 0.05 O 2 platelet particles analyzed by total electron yield (TEY)/total fluorescence yield (TFY) spectroscopy, ptychography, and SX-STM were synthesized hydrothermally followed by calcination. Ni­(NO 3 ) 2 ·6H 2 O, Co­(NO 3 ) 2 ·6H 2 O, and Al­(NO 3 ) 3 ·9H 2 O were combined in a molar ratio equal to 80:15:5 in 70 mL of H 2 O. NaOH was added to the mixture to achieve a 2:1 OH – /TM ratio.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The product was washed with water, dried completely, and annealed for 4 h at 400 °C to remove the double layered hydroxide structure . The resulting oxide was mixed with LiOH·H 2 O such that x = 1 in Li x Ni 0.8 Co 0.15 Al 0.05 O 2 and calcined at 800 °C for 1 h followed by 700 °C for 12 h. The material was structurally characterized using a Bruker D8 Advance X-ray diffractometer with Cu Kα radiation (Figure S1) and matched to prior literature data for LiNi 0.8 Co 0.15 Al 0.05 O 2 . , Pawley refinement was performed using GSAS-II, resulting in refined cell parameters of a = 2.865 Å and c = 14.170 Å. A previously reported diffraction study for these synthesis conditions reported ≈2.7% Ni occupancy in Li sites .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In this work, we developed an ultra-microtome-based method for the preparation of TEM specimens from lithium transition metal oxides (battery cathode particles). Cathode materials are widely synthesized by a precipitation process involving primary particles and secondary particles (May et al, 2018; Zhang et al, 2018; Boesenberg et al, 2019). Primary particles normally have a size in the hundred nanometer range, and secondary particles usually have a particle size in the micrometer scale.…”
Section: Introductionmentioning
confidence: 99%